PROBLEM-BASED MOBILE LEARNING IN COMMUNITY MEDICINE: AN INTERVENTIONAL STUDY IN PHASE II MBBS STUDENTS - SUKLA, PRADEEP; KUMAR, SANJEEV; YADAV, SACHIN SINGH; GUPTA, SHUBHANSHU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: (1) The aim of the study was to compare the effectiveness of problem-based learning (PBL) in classroom and problem-based mobile learning using a mobile application (PBML) and (2) to study the perception of students to problem-based m-learning (PBML) and problem-based learning (PBL) in classroom. Methods: After getting clearance from Institutional Ethics Committee, an interventional study was conducted for a period of 2 months among 150 Phase II MBBS students of Government Medical College, Datia (MP). Students who gave consent for the study were divided into two groups, namely, R-1 and R-2, and analyzed for the effectiveness of problem-based mobile-learning (PBML) as a teaching learning method in comparison with problem-based learning in classroom (PBL). Perception of students toward use of PBML and PBL as teaching learning method was collected using validated questionnaire. Results: It was observed from the study that in all the sessions, post-test mean scores were significantly higher than pre-test scores in both PBL and PBML. Before the intervention, there was no significant difference in the pre-test mean scores in topics done by PBL and PBML. After intervention, the only the post-test mean scores significantly improved. When the total post-test scores of PBL and PBML compared, it was found that PBML mean score is significantly higher than PBL mean score. In the student’s perception analysis, it was found that both methods are effective in concept building, stimulating, helpful in passing examinations, and development of problem-learning skills. Conclusion: From the study finding, we can conclude that both PBL and PBML are effective modes of teaching applied community medicine for Phase II MBBS students. PBML is more effective than PBL in teaching applied community medicine in Phase II MBBS students. Perception analysis shows that interaction with the students and doubt clearance is more effectuated with PBL than PBML.